2003
DOI: 10.1046/j.1439-0450.2003.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Climate on the Presence of Culicoides imicola in Italy

Abstract: A model was developed to classify the Italian territories in relation to their suitability to harbour populations of Culicoides imicola and, as a consequence, also able to sustain a bluetongue (BT) epidemic. Italy was subdivided into 3507 10 x 10 km cells. In 546 cells at least one collection was made. The cell was considered the unit for all subsequent analyses. Culicoides were collected using Onderstepoort-type blacklight traps. Some traps were operated weekly at chosen sites; the remainder were moved almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 10 publications
3
48
2
Order By: Relevance
“…However, the monthly biting rate of C. fulvithorax was not correlated with temperature in this study. A previous study showed that temperature and relative humidity, vis-à-vis Culicoides occurrence, are independent variables (Conte et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the monthly biting rate of C. fulvithorax was not correlated with temperature in this study. A previous study showed that temperature and relative humidity, vis-à-vis Culicoides occurrence, are independent variables (Conte et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, literature is replete with information on studies on these insects from different parts of the world (Noireau et al, 1990;Conte et al, 2003;Mercer et al, 2003). To the best of our knowledge, most of the previous Culicoides studies from Nigeria were associated with wild or domestic animals (Dipeolu, 1976a(Dipeolu, , 1976bDipeolu and Ogunrinade, 1977;Udonsi, 1988), and none assessed human biting rates.…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators (67,68) have, however, remained circumspect about the mooted continuing northward range expansion of C. imicola, proposing instead that, in the past, it had simply been overlooked, due to its mosaical distribution and narrow seasonality (August to November), exacerbated by inferior surveillance tools and sporadic, short-term collecting efforts. Indeed, in Italy at least, C. imicola would appear to be in stasis as it has shown no expansion whatsoever in its range since the year 2000, when Italy implemented its large-scale vector surveillance programme, which has been maintained continuously ever since (69).…”
Section: Climatic Factors and Culicoidesmentioning
confidence: 99%
“…24 Bluetongue viruses have received considerable attention in this regard, although most efforts have focused on Europe, Africa, and Australia. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] In North America there have been efforts to study the relationship between BTV in cattle and environmental or climatic variables. Seroconversion to BTV in cattle, based on a microimmunodiffusion test, was modeled using several variables related to temperature, precipitation, and humidity in Alabama.…”
Section: Introductionmentioning
confidence: 99%